Erysiphe jiangxiensis sp. nov. associated with powdery mildew on Castanopsis sclerophylla in Jiangxi, China - Zhang, Haiyan; Xie, Feng; Shu, Qiwen; Luan, Zhiyuan; Li, Dong; Luan, Fenggang (Phytotaxa, 2025)
Between 2020 and 2023, Castanopsis sclerophylla, an evergreen broad-leaved tree native to southern China, exhibited powdery mildew symptoms on mature trees in Nanchang, Jiangxi province, with an incidence rate of 50% to 75%. Microscopic examination of the sexual morph revealed that the fungus differed from Erysiphe kissiana by having smaller chasmothecia, and fewer asci and ascospores. These findings were supported by maximum likelihood analysis and Bayesian inference, which showed low bootstrap support and Bayesian posterior probabilities. Based on morphological differences and molecular phylogenetic analysis, we identified this fungus as a new species, Erysiphe jiangxiensis. The pathogenicity of E. jiangxiensis on C. sclerophylla was confirmed using modified Koch’s postulates. The discovery of E. jiangxiensis has significant implications for identifying powdery mildew species on Chinese tanbark-oak and for disease management.